A revision of Cryptocarya R. Br. (Lauraceae) of Peninsular Malaysia. Issue 1 (March 2016) - Kok, R.
Summary A revision of the Peninsular Malaysia species ofCryptocarya (Lauraceae) is presented with a summary of its taxonomic history, keys, full descriptions, distribution maps, conservation assessments, ecological data, ethno-botanical notes and a delineation of its key morphology. Through this analysis 17 distinct species are recognised, two names are lectotypified (C. bracteolata andC. costata ), and four names are placed into synonymy for the first time. One species, C. malayana having been misidentified for a century, is described here for the first time. Most species described are considered to be common and three as endangered (C. bracteolata ;C. malayana andC. wrayi ).